Tingkat Pemahaman Orang Tua terhadap Pendidikan Seksualitas pada Anak Usia Dini - Itoh Masitoh; Ade Hidayat (Universitas Mathla'ul Anwar Banten, 2020)
PARENTS’ UNDERSTANDING LEVEL OF SEXUALITY EDUCATION IN EARLY CHILDHOODS. Sexuality education is very important considering the many cases that occur regarding sexual violence against children and adolescents. Sex education is an effort to teach, raise awareness, and provide information about sexual problems. The information provided includes knowledge about the function of the reproductive organs by instilling morals, ethics, commitment, religion so that there is no “abuse” of the reproductive organs. Sex education is very important to be given from an early age. Knowledge of sex in children can prevent sexual deviations in children. Sex education in children can also prevent children from becoming victims of sexual harassment, by being equipped with knowledge about sex, they can understand which behavior is considered sexual harassment. There are four methods of providing early childhood sex education, namely: 1) giving an understanding of sex to children based on religion; 2) Communication between family members about sex; 3) Adjustment of the explanation of sex education with the level of understanding of the child; and 4) Restrictions on answering questions about sex to children. Of the four methods, only the first method worked relatively well, while the other three methods did not work well, where the parental consent rate was less than 50%, so it really needs to be improved.